Comparison of Salivary Calcium Level in Dentulous and Edentulous Patients - Rabiei, Maryam; Asli, Hamid Neshandar; Mohamadi, Mohadeseh Haji (European Journal of Dentistry, 2019)
Objectives Calcium is an inorganic component of the saliva, which is especially important in oral and dental health. This study sought to compare unstimulated salivary calcium level of dentulous and edentulous patients.Materials and Methods This case–control study was conducted on 72 participants, including 36 dentulous and 36 edentulous patients. The unstimulated salivary flow rate of patients and the mean salivary calcium concentration were measured and compared. The data were analyzed using the nonparametric Mann–Whitney U-test.Results The mean age of participants was 56.3 years. The mean number of teeth was 18.9 in the dentulous group. No significant difference was noted in salivary calcium level of dentulous and edentulous patients. The mean salivary calcium concentration was 0.61 ± 0.3875 mmol/L in dentulous and 0.8025 ± 0.5975 mmol/L in edentulous patients. Salivary calcium level had a significant inverse correlation with salivary flow rate (r = –0.370, p = 0.027), and by every 1-unit increase in salivary flow rate, salivary level of calcium significantly decreased by 3.85 units.Conclusion Edentate had averagely higher salivary calcium level compared to dentulous. The salivary concentration of calcium ion is not correlated to the presence or absence of teeth. Salivary flow rate reduces the calcium concentration.
Keywords: atomic absorption spectrophotometry; calcium; dental health survey; edentulous; mouth; saliva